Analisa Kualitas Aplikasi WTR Application Vendor Excellence (TRACE) PT Waskita Toll Road Dengan Metode Heuristic Evaluation - Lestiawan, Rendik Juhan; Rakhmah, Syifa Nur (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics; Vol 9 No 2 (2024): INFORMATICS FOR EDUCATORS AND PROFESSIONAL : JOURNAL OF INFORMATICS (Desember 2024), 2024)
ABSTRACT   Rendik Juhan Lestiawan (11220867) , Quality Analysis of PT Waskita Toll Road's WTR Application Vendor Excellence (TRACE) Application with the Heuristic Evaluation Method.   Procurement of Goods and Services is a process to meet the needs of goods and services according to regulations. At PT Waskita Toll Road, the Goods and Services Procurement process involves partner management and provider performance evaluation. One important component of digitization is the Vendor Management System (VMS).  WTR Application Vendor Excellence (TRACE) is an application that facilitates the management of goods and services providers at PT Waskita Toll Road. However, this application faces problems related to an unattractive interface and reduces user interest. This research while assessing TRACE user satisfaction, used the Heuristic Evaluation Method to identify interface problems. The goal is to get identification and recommendation suggestions from the application to make it more comfortable and easy to use. The main data collection uses questionnaire media to 80 respondents who use the TRACE application and data processing is done using SPSS and calculations using a Likert scale. Based on the results of data processing, it can be seen that the results of user perceptions of convenience, information quality and interaction quality are included in the category of good interval value range. From the results of research with 10 aspects of heuristic evaluation for the aspects of Help and Documentation getting the lowest average score, so it needs to be improved even though it is currently not too annoying for users.     Keywords: Quality Analysis, TRACE Application PT Waskita Toll Road, Heuristic Evaluation Method, SPSS, Likert Scale